2022
DOI: 10.1088/1361-6463/ac7c44
|View full text |Cite
|
Sign up to set email alerts
|

A state-of-art review on gallium oxide field-effect transistors

Abstract: As a promising ultra-wide bandgap (UWBG) semiconductor, gallium oxide (Ga2O3) has recently aroused increasing attention in the area for high-power electronics, power switch for radio frequency (RF) operation, and solar blind UV detectors. The β-phase of Ga2O3 is deemed as a potential candidate for next generation high-power electronics due to its high theoretical breakdown electric field (8 MV cm−1), UWBG (4.8 eV), and large Baliga’s figure of merit. Owing to the intensive research efforts across the world sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 140 publications
0
7
0
Order By: Relevance
“…Calculations suggest the absence of shallow acceptors in Ga 2 O 3 , and holes exhibit self-trapping effects within the material [31,32]. Consequently, current research is primarily focused on unipolar Ga 2 O 3 power electronic devices, including field-effect transistors (FETs) and Schottky barrier diodes (SBDs) [33][34][35]. Compared to traditional p-n junction diodes, SBDs exhibit lower turn-on voltages and faster recovery times, making them commonly employed in low-power and high-speed switching applications.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations suggest the absence of shallow acceptors in Ga 2 O 3 , and holes exhibit self-trapping effects within the material [31,32]. Consequently, current research is primarily focused on unipolar Ga 2 O 3 power electronic devices, including field-effect transistors (FETs) and Schottky barrier diodes (SBDs) [33][34][35]. Compared to traditional p-n junction diodes, SBDs exhibit lower turn-on voltages and faster recovery times, making them commonly employed in low-power and high-speed switching applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2D Ga 2 O 3 with a wide bandgap (4.69-6.42 eV) and extraordinary properties 2,3 have shown superior device performance over the bulk counterpart β-Ga 2 O 3 for applications of photodetectors, [4][5][6][7] gas sensors, 8,9 and field-effect transistors (FET). [10][11][12][13][14] Subsequent theoretical studies predict that the electron mobility of ML Ga 2 O 3 is as high as 2684 cm 2 V −1 s −1 , which can be further tuned up to ∼10 4 cm 2 V −1 s −1 by the layer thickness and surface passivation, 15,16 and high stability is maintained in the ambient atmosphere. In addition, defect-free oxygen vacancy and valid p-type doping ML Ga 2 O 3 is expected to achieve through valence band modification, which breaks the obstruction of bulk β-Ga 2 O 3 caused by the serious self-compensating effect; 17,18 hence, the development of complementary logic applications based on ML Ga 2 O 3 is expected to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous review articles on β-Ga 2 O 3 FETs have reported the chronological development in device design and performance [10], or focused specifically on RF FETs [7], E-mode FETs [11], or vertical GaN and β-Ga 2 O 3 FETs [9]. Other review papers have covered FETs designed for both high-power and RF applications [12,13]. This review is formatted to aid current and future β-Ga 2 O 3 high-power and RF FET researchers by separately discussing the different steps of FET fabrication, ranging from structures, materials, ohmic contacts, gate dielectrics, and material preparation.…”
Section: Introductionmentioning
confidence: 99%